The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
CALL in a Climate of Change: Adapting to Turbulent Global Conditions – Short Papers From EUROCALL 2017 2017
DOI: 10.14705/rpnet.2017.eurocall2017.702
|View full text |Cite
|
Sign up to set email alerts
|

Teacher perspectives on the integration of mobile-assisted language learning

Abstract: Mobile-Assisted Language Learning (MALL) provides second language (L2) learners and teachers with resources to enhance the learning experience, including its anytime, anywhere accessibility (Traxler, 2007). However, factors such as lack of confidence with technology (Son, 2014) and time limitations (Godwin-Jones, 2015) may prevent teachers from implementing MALL successfully. To better understand the barriers to using MALL, this pilot study investigated the perspectives of 21 L2 English teachers at secondary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…In a similar way, [25] explain that the pedagogical limitations involve the lack of students' concentration and work interruption when using mobile devices. [26] also indicate that concerns about distraction, classroom disruption as well as potential cheating may also have an impact on teachers' decision to allow using mobile devices in the classroom. [27] Maintain that a contradictory tendency is happening in higher education at the momentdespite the fact that cell phones and other mobile devices are completely embedded in the life of students, instructors normally see these devices, cell phones in particular, as something that causes distractions, and is unnecessary for learning purposes.…”
Section: Mobile Technologies and Learner Distractionmentioning
confidence: 99%
“…In a similar way, [25] explain that the pedagogical limitations involve the lack of students' concentration and work interruption when using mobile devices. [26] also indicate that concerns about distraction, classroom disruption as well as potential cheating may also have an impact on teachers' decision to allow using mobile devices in the classroom. [27] Maintain that a contradictory tendency is happening in higher education at the momentdespite the fact that cell phones and other mobile devices are completely embedded in the life of students, instructors normally see these devices, cell phones in particular, as something that causes distractions, and is unnecessary for learning purposes.…”
Section: Mobile Technologies and Learner Distractionmentioning
confidence: 99%
“…Classroom activities were supported by reading e-books that contained Phonology subject, playing audio and video file to get visualization of the Phonological concept, and operating offline dictionary. Grimshaw, Cardoso, and Collins (2017) reported that most language teachers were opened to engage their students in MALL, but they still worried with the limitation of MALL.…”
Section: Introductionmentioning
confidence: 99%
“…The speech recognition function should be improved. The satisfaction analysis of the speech DB-CALL system is similar to that of the online survey of speech assisted language learning of Grimshaw, Cardoso, and Collins (2017). If technology of speech recognition improves further, the satisfaction level of Table 3 below will be higher.…”
Section: Learners' Satisfactionmentioning
confidence: 79%